2023
DOI: 10.3390/su15075795
|View full text |Cite
|
Sign up to set email alerts
|

Telling Our Story—A Community-Based Meso-Level Approach to Sustainable Community Development

Abstract: Engaging diverse stakeholders in dialogue around sustainable development has proven to be a successful strategy to advance sustainable development goals. Without local engagement, sustainable development efforts can fail to accomplish their objectives. Yet, determining the best strategy for engaging diverse stakeholders can be challenging. Similarly challenging can be the transfer of information regarding successful development strategies from one community to another. Local specificity is key to finding susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…They are health, education, social and cultural amenities, environment quality and recreation, and IT and transportation access. In addition, the model engages local stakeholders in the planning, implementation, and coordination process around a qualitative storytelling workshop that engages community members in envisioning the future with respect to the five domains [20,21]. The W8CED framework is a community-led approach that is hyperlocal and engages residents in six key areas of community need.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are health, education, social and cultural amenities, environment quality and recreation, and IT and transportation access. In addition, the model engages local stakeholders in the planning, implementation, and coordination process around a qualitative storytelling workshop that engages community members in envisioning the future with respect to the five domains [20,21]. The W8CED framework is a community-led approach that is hyperlocal and engages residents in six key areas of community need.…”
Section: Methodsmentioning
confidence: 99%
“…The Five Pillars Model [20,21] and the W8CED [22] framework are multidisciplinary development frameworks aiming to empower and mobilize individuals, groups, and organizations to take collective action towards positive social change. At their core, both community development approaches seek to improve the quality of life of individuals and communities by addressing issues related to poverty, inequality, social exclusion, and marginalization.…”
Section: Meso-level Vs Micro-level Approachmentioning
confidence: 99%
“…It argues that different stakeholders leave their distinct mark on the selection of indicators to measure development success (O'Hara, 1999). Some in the urban studies field have therefore raised concerns about development approaches that lack local engagement and decimate the economic and social fabric of neighborhoods (Perry, 2020;O'Hara et al, 2023). Others recognize that urban planners and developers may not see sufficient value in investing the time and resources necessary to establish a meaningful local engagement process, especially given the opportunity costs associated with scarce urban resources (Blanke and Walzer, 2013).…”
Section: Participation In Development and Planningmentioning
confidence: 99%
“…In the field of urban planning, stakeholders are organizations, groups, and individuals that can impact, are impacted by, or believe they can influence a project's design, directions, or outcomes (Project Management Institute, 2021). In development, particularly sustainable development, engaging stakeholders requires a delicate balancing act between economic, environmental, and societal conditions (Rondinel-Oviedo and Schreier-Barreto, 2018;O'Hara et al, 2023). The community development literature suggests that planners, local governments, and developers follow a traditional method of stakeholder engagement (Bhattacharyya, 2004;Hampton et al, 2024).…”
Section: Participation In Development and Planningmentioning
confidence: 99%
“…Social capital produces equality, viewed as a sign of 'judicial equity'. According to O'Hara's analysis of these disparities, specific individuals of society bear heavier sink capacity than others and are disproportionately exposed to the adverse effects of tiredness, stress, and pollution [20]. Following 25 years of research, British scientist Michael Marmot concluded that 'the chances you have for full social involvement and participation are vital for health, wellbeing, and lifespan' [15]: "Responding to the needs of the neighborhood community to encourage an equitable division of rewards and responsibilities, encouraging underprivileged groups to engage in fair commerce, respect for human rights, and other equity-related behaviors.…”
Section: Social Capital Link To Wellbeing and Social Impactmentioning
confidence: 99%